(untitled) (Research, Society and Development, 2021)
The aim of this paper is to present a quick and practical review of the literature on the particularities of general anesthesia for dogs and cats with ophthalmopathies, making a brief report of the main considerations that the anesthesiologist should have in view of patients with ocular changes. Barbiturates, propofol, α2-adrenergic receptor agonists, benzodiazepines, phenothiazines and opioids are often used in protocols for general anesthesia of ophthalmic surgical procedures in dogs and cats, which may promote changes in intraocular pressure, tear production, pupil size, in eye centering, in the eyelid, corneal and oculocardiac reflexes. The elaboration of an anesthetic protocol for a specific patient involves not only the appropriate choice of anesthetic agent, but also a management plan capable of assuring the quality of the postoperative result. This requires knowledge of the patient’s physical condition and the specific ophthalmic procedure to be performed, as well as familiarity with ocular physiology and pharmacology.